You are on page 1of 7

1- (a) Prove that: x|n(xx|n 0) = 2 ]

n
(x) stnn0

n=1,3,5,

(b) Show that: ]3
2
(x) = _
2
ax
[
stnx-xus x
x

(c) Use the generating function of Legendre polynomials to prove that:
(n +1)P
n+1
(x) = (2n +1) x P
n
(x) - nP
n-1
(x)
(d) Use the substitution: x = cux z to reduce the differential
equation:
d
2
y
dz
2
+
us z
stnz
dy
dz
+n(n +1) y = to Legendres
equation and hence find its general solution.

2- (a) Find a general solution of:
0
2
u
0x
2
-
0
2
u
0x dy
+9
0
2
u
0y
2
=
(b) Solve
0u
0t
= 4
0
2
u
0x
2
, u(, t) = 3, u(1, t) = 5, u(x, ) = 2x +4

3- (a) Find the vibrations of a circular drumhead of radius 2 if the governing
equation is
0
2
u
0t
2
= 1[
0
2
u
0r
2
+
1
r

0u
0r
, the initial velocity is 0, and the
initial displacement is f(r) = 4- r
2
.

(b) Solve u
tt
= u
xx
+ u
yy
, where
u(, y, t) = u(a, y, t) = , u(x, , t) = u(x, a, t) = , if
u(x, y, ) = . 1stn3x stn4y -. 2 x|n 5x x|n 12y, u
t
(x, y, ) =

Third Year (Elec.) EMP 301
Engineering Mathematics (4)
Final Term Exam

Jan. 2011
Zagazig University
Faculty of Engineering
Eng. Math.& Physics Dept.


Time Allowed : three hours

Full Marks: ( 100)


Answer All Questions
5M

5 M
5 M
8M
6 M
8 M
5 M
Good Wishes Professor: Salwa Amin PTO
8 M
Solution
1 a) Prove that: x|n(xx|n 0) = 2 ]
n
(x) stnn0

n=1,3,5,

Let t = c
0
-
1
t
= c
-0
, then t -
1
t
= 2i sin 0 and the generating
function
c
x
2
[t-
1
t

= c
x sIn0
= cos(x sin0) +i sin(x sin 0) = [
n
(x)

n=-
c
n0

Since [
-n
(x) = (-1)
n
[
n
(x) then
[
-n
(x)c
-n0
= (-1)
n
[
n
(x) c
-n0


[
n
(x)c
n0
+ [
-n
(x)c
-n0
= [
n
(x)|c
n0
+(-1)
n
c
-n0
]
= _
2 i [
n
(x) sin n0 n = 1, S,
2 [
n
(x) cos n0 n = 2, 4,


cos(x sin0) +i sin(x sin0) =
= [
0
(x) +2 [
n
(x) cos n0 +2i [
n
(x) sinn0

n=1,3,5,

n=2,4,6,


Equating imaginary parts in both sides, then we obtain

sin(x sin0) = 2 [
n
(x) sinn0

n=1,3,5,



1- (b) Show that: ]3
2
(x) = _
2
ax
[
stnx-xus x
x


Put n=1/2 in [
n+1
(x) + [
n-1
(x) =
2n
x
[
n
(x) , then [3
2
(x) + [
-
1
2
(x) =
1
x
[1
2
(x)
Since [

1
2
(x) = _
2
nx
sin x, [
-
1
2
(x) = _
2
nx
cos x, then

[3
2
(x) =
1
x
_
2
nx
sin x -
_
2
nx
cos x =
_
2
nx
_
sinx x cos x
x
]

5 M
5 M
1- (c) Use the generating function of Legendre polynomials to prove that:
(n +1)P
n+1
(x) = (2n +1) x P
n
(x) - nP
n-1
(x)
Starting from the generating function
1
1-2xt+t
2
= P
n
(x)t
n
n=0

and differentiating with respect to t, we get
x -t
(1 -2xt +t
2
)
32
= n P
n
(x)

n=0
t
n-1

===
x -t
1 -2xt +t
2
= (1 - 2xt +t
2
) n P
n
(x)

n=0
t
n-1

x -t
1 -2xt +t
2
= (x -t)P
n
(x)

n=0
t
n
= (1 - 2xt + t
2
) n P
n
(x)

n=u
t
n-1

x P
n
(x)

n=0
t
n
- P
n
(x)

n=0
t
n+1
= n P
n
(x)

n=0
t
n-1
- 2nx P
n
(x)

n=0
t
n
+ n P
n
(x)

n=0
t
n+1

Equating the coefficients of t
n
on each side, we find
x P
n
(x) - P
n-1
(x) = (n +1) P
n+1
(x) - 2nx P
n
(x) + (n -1) P
n-1
(x)
which yields the required result: (n +1)P
n+1
(x) = (2n +1) x P
n
(x) -nP
n-1
(x)

1- (d) Use the substitution: x = cux z to reduce the differential
equation:
d
2
y
dz
2
+
us z
stnz
dy
dz
+n(n +1) y = to Legendres equation and hence
find its general solution.
x = cos z =
dx
dz
= -sin z
dy
dz
=
dy
dx

dx
dz
= -sin z
dy
dx

d
2
y
dz
2
=
d
dz
[-sinz
dy
dx
= -jsin z
d
dz
[
dy
dx
+cos z
dy
dx
[ = -jsinz
d
2
y
dx
2

dx
dz
+cos z
dy
dx
[ =
j(1 -x
2
)
d
2
y
dx
2
-x
dy
dx
[
where we have substituted, sin
2
z = 1 cos
2
z = 1 x
2
.

Substitution in the given equation yields the Legendre equation
j(1 -x
2
)
d
2
y
dx
2
-x
dy
dx
[ - x
dy
dx
+n(n +1) y = u , or
(1 -x
2
)
d
2
y
dx
2
-2x
dy
dx
+n(n +1) y = u
The general solution of Legendre's differential equation can be written as
y(x) = CP
n
(x) +
n
(x), y(z) = CP
n
(cos z) +
n
(cos z)
5 M
5 M
2- (a) Find a general solution of:
0
2
u
0x
2
-
0
2
u
0x dy
+9
0
2
u
0y
2
=
Assume u = c
ux+b
. Substituting in the given equation, we find
o
2
c
ux+b
- 6 ob c
ux+b
+ 9 b
2
c
ux+b
= u
o
2
-6ob +9b
2
= u - (o -Sb)
2
= u - o = Sb, Sb (repeated roots)
Thus, the solution is given by u = c
b(3x+)
and so u = F(Sx +y) is a
solution. By analogy with repeated roots for ordinary differential equations we
might be led to believe that x G(Sx +y)or y G(Sx +y) to be another
solution. Thus a general solution is
u = F(Sx +y)+ x G(Sx +y) or u = F(Sx +y)+ y G(Sx +y)

6 M
2- (b) Solve
0u
0t
= 4
0
2
u
0x
2
, u(, t) = 3, u(1, t) = 5, u(x, ) = 2x +4
The problem has nonhomogeneous boundary conditions u(u, t) = S, u(1, t) = S in
place of the homogeneous ones.
Let u(x, t) = :(x, t ) +(x) where (x) is to be suitably determined.
The given differential equation becomes

o(:(x, t ) +(x))
ot
= 4
o
2
(:(x, t ) +(x))
ox
2

-
o:
ot
= 2_
o
2
:
ox
2

+ _,
with the conditions:
_
u(u, t ) = :(u, t ) +(u) = S,
u(1, t ) = :(1, t ) +(1) = S,
u(x, u ) = :(x, u ) +(x) = 2x +4

This can be simplified by choosing:

= u, (u) = S, (1) = S
from which we find

= u -

= c
1
- = c
1
x +c
2

(u) = S = c
2
, (1) = S = c
1
+S - c
1
= 2 - (x) = 2x +S
The resulting boundary value problem in :(x, t ) is given by:

t
= 4

2

x
2

,

:(u, t ) = u, :(1, t ) = u, :(x, u ) = u(x, u )
_____
2x+4
-(x)
_
2x+3
= 1

Let :(x, t) = X(x) I(t). Then,
o:
ot
= 2
o
2
:
ox
2

- X I

= 2X

I
ddng b 2X1
============
I'
4I
=
X''
X
= c

==
I'
4I
=
X''
X
= -z
2

I
i
= -4z
2
I - I(t) = kc
-4x
2
t

X'
i
+z
2
X = u - X(x) = o cos zx +b sinzx

:(x, t) = X(x) I(t) = c
-2x
2
t
(A cos zx +Bsinzx)
Since :(u, t) = u = c
-2x
2
t
(A ) - A = u, then :(x, t) = Bc
-2x
2
t
sinzx
Since v(1, t ) = 0 = Bc
-4x
2
t
sin z, - z = nn, n = 1,2,
:(x, t) = B
n
c
-4(nn)
2
t
sin nnx

n=1
, By the initial condition
:(x, u) = B
n
sin nnx

n=1
= 1 - B
n
=
2
1
_ sin nnx Jx =
1
0
2
nn
(1 -cos nn)
:(x, t) =
2
n

1
n
(1 -cos nn) c
-4(nn)
2
t
sin nnx

n=1

u(x, t) =
2
n

1
n
(1 -cos nn) c
-4(nn)
2
t
sin nnx

n=1
+2x +S

8 M
3- (a) Find the vibrations of a circular drumhead of radius 2 if the governing
equation is
0
2
u
0t
2
= 1[
0
2
u
0r
2
+
1
r

0u
0r
, the initial velocity is 0, and the
initial displacement is f(r) = 4- r
2
.
We have: BCs: u(2, t) = u, ICs: u(r, u) = (r) = 4 - r
2
, u
t
(r, u) =
u,
Let u(r, t) = R(r) T(t)
I

4
2
I
=
1
R
_R'' +
1
r
R'] = -z
2

I

+4
2
z
2
I = u, r
2
R
ii
+r R
i
+z
2
r
2
R = u
I

+4
2
z
2
I = u

== I(t) = A cos 4zt +Bsin 4zt
r
2
R
ii
+r R
i
+z
2
r
2
R = u - R(r) = C [
0
(zr) +
0
(zr)
The functions [
0
and
0
are the Bessel functions of the first and second kind. But

0
becomes infinite at r=0, so D=0 - R(r) = C [
0
(zr)
On the boundary r=2 we get R(2)= C [
0
(2z)=0
2z = o
1
, o
2
, o
3
,

= z
n
=
u
n
2
, n = 1, 2, S,
u(r, t) = (A
n
cos 2o
n
t +B
n
sin2o
n
t) [
0
[
o
n
2
r

n=1

Now, apply the second IC: u
t
(r, u) = u, - B
n
=
Applying the first IC: u(r, u) = (r) = 4- r
2
= A
n
[
u
[
o
n
2
r

n=1

A
n
=
2
4]
1
2
(u
n
)
] r (r)
2
0
[
0
[
u
n
2
r Jr =
2
4]
1
2
(u
n
)
] r (4 - r
2
)
2
0
[
0
[
u
n
2
r Jr=
=
2
4[
1
2
(o
n
)
2
u
n
_(4 - r
2
) _r [
1
[
o
n
2
r__
0
2
+2 _ r
2
2
0
[
1
[
o
n
2
r Jr _ =
=
2
4[
1
2
(o
n
)
_
2
u
n
]
2
j2 r
2
[
2
[
o
n
2
r [
0
2
=
4
o
n
2
[
1
2
(o
n
)
4[
2
(o
n
)

Since [
2
(o
n
) =
2
u
n
[
1
(o
n
) -[
0
(o
n
) =
2
u
n
[
1
(o
n
)
Finally we get the solution u(r, t) =
32
u
n
3
]
1
(u
n
)
cos (2o
n
t) [
0
[
u
n
2
r

n=1


8M
3- (b) Solve u
tt
= u
xx
+ u
yy
, where
u(, y, t) = u(a, y, t) = , u(x, , t) = u(x, a, t) = , if
u(x, y, ) = . 1stn3x stn4y -. 2 x|n 5x x|n 12y, u
t
(x, y, ) =
Let: u(x y, t) = X(x) Y (y) T(t). Substitution into PDE gives
X I

= (X'' I +X '' I)
DIvIdIng by X1
============
I

I
=
X''
X
+
''

= -z
2

I

+c
2
z
2
I = u

=====I = Acos czt + Bsinczt

X
ii
X
= --z
2
-

ii

= -v
2

=====_
X'' +v
2
X = u

ii
+(z
2
-v
2
) = u

Let z
2
-v
2
= p
2
, or equivalently z
2
= p
2
+v
2

X'' +v
2
X = u

=====X = C cos vx + sinvx
'' +p
2
= u

===== = E cos py + 0 sinpy
u(x, y, t) = (C cos vx + sinvx)(E cos py + 0 sin py)(Acos czt +
Bsinczt
)
BCs: u = 0 on the boundary of the rectangle reads:
u(u, y, t) = u(x, u, t) = u(l, y, t) = u(x, b, t) = u
u(u, y, t) = u

=====C = u
u(x, u, t) = u

=====E = u
u(n, y, t) = u

=====sinvn = u

=====v = n, n = 1,2,S,
u(x, n, t) = u

=====0 sinpn = u

=====p = m, m = 1,2,S,
u(x, y, t) = sinnx sinmy (A
nm
cos z
mn
t + B
nm
sinz
mn
t)

m=1

n=1
,
z
mn
= n
2
+m
2
= , n = 1,2,S, , m = 1,2,S,
The initial velocity condition u
t
(x, y, u) = u - B
nm
= u
From the initial deflection condition
u(x, y, u) = u.1sin Sx sin 4y -u.2 sin Sx sin 12y = A
nm

m=1

n=1
sinnx sinmy
A
nm
= u , unles foi (n = S, m = 4, anu hencez
nm
= S , A
nm
= u.1)anu
(n = S, m = 12, onJ bcnccz
nm
= 1S , A
nm
= -u.2)
The required solution is:
u(x, y, t) = u.1 sinSx sin4y (cos St) -u.2 sinSx sin12y (cos 1St)

8 M